Susceptibility of swine to H5 and H7 low pathogenic avian influenza viruses - Balzli, C.; Lager, K.; Vincent, A.; Gauger, P.; Brockmeier, S.; Miller, L.; Richt, Juergen A.; Ma, Wenjun; Suarez, D.; Swayne, D. E. (My University, 2016)
Background: The ability of pigs to become infected with low pathogenic avian influenza (LPAI) viruses and then generate mammalian adaptable influenza A viruses is difficult to determine. Yet, it is an important link to understanding any relationship between LPAI virus ecology and possible epidemics among swine and/or humans. Objectives: Assess susceptibility of pigs to LPAI viruses found within the United States and their direct contact transmission potential. Methods: Pigs were inoculated with one of ten H5 or H7 LPAI viruses selected from seven different bird species to test infectivity, virulence, pathogenesis, and potential to transmit virus to contact pigs through histological, RRT-PCR and seroconversion data. Results: Although pigs were susceptible to infection with each of the LPAI viruses, no clinical disease was recognized in any pig. During the acute phase of the infection, minor pulmonary lesions were found in some pigs and one or more pigs in each group were RRT-PCR-positive in the lower respiratory tract, but no virus was detected in upper respiratory tract (negative nasal swabs). Except for one group, one or more pigs in each LPAI group developed antibody. No LPAI viruses transmitted to contact pigs. Conclusions: LPAI strains from various bird populations within the United States are capable of infecting pigs. Although adaptability and transmission of individual strains seem unlikely, the subclinical nature of the infections demonstrates the need to improve sampling and testing methods to more accurately measure incidence of LPAI virus infection in pigs, and their potential role in human-zoonotic LPAI virus dynamics. © 2016 John Wiley & Sons Ltd.
Citation: Balzli, C., Lager, K., Vincent, A., Gauger, P., Brockmeier, S., Miller, L., . . . Swayne, D. E. (2016). Susceptibility of swine to H5 and H7 low pathogenic avian influenza viruses. Influenza and other Respiratory Viruses. doi:10.1111/irv.12386
Keywords: Avian Influenza; H5; H7; Infection; Low Pathogenic; Swine Susceptibility